Explicit and implicit issues in the developmental cognitive neuroscience of social inequality - D'angiulli, Amedeo; Lipina, Sebastian J.; Olesinska, Alice (Frontiers in Human Neuroscience, 2012)
The appearance of developmental cognitive neuroscience (DCN) in the socioeconomic status (SES) research arena is hugely transformative, but challenging. We review challenges rooted in the implicit and explicit assumptions informing this newborn field. We provide balanced theoretical alternatives on how hypothesized psychological processes map onto the brain (e.g. problem of localization) and how experimental phenomena at multiple levels of analysis (e.g. behaviour, cognition and the brain) could be related. We therefore examine unclear issues regarding the existing perspectives on poverty and their relationships with low SES, the evidence of low-SES adaptive functioning, historical precedents of the “alternate pathways” (neuroplasticity) interpretation of learning disabilities related to low-SES and the notion of deficit, issues of “normativity” and validity in findings of neurocognitive differences between children from different SES, and finally alternative interpretations of the complex relationship between IQ and SES. Particularly, we examine the extent to which the available laboratory results may be interpreted as showing that cognitive performance in low-SES children reflects cognitive and behavioural deficits as a result of growing up in specific environmental or cultural contexts, and how the experimental findings should be interpreted for the design of different types of interventions – particularly those related to educational practices - or translated to the public – especially the media. Although a cautionary tone permeates many studies, still, a potential deficit attribution –i.e., low-SES is associated with cognitive and behavioral developmental deficits – seems almost an inevitable implicit issue with ethical implications. Finally, we sketch the agenda for an ecological DCN, suggesting recommendations to advance the field, specifically, to minimize equivocal divulgation and maximize ethically responsible translation.